2004
DOI: 10.1080/13546800344000039
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension, encoding, and monitoring in the production of confabulation in memory: A study with schizophrenic patients

Abstract: The results are in favour of the hypothesis that verbal comprehension difficulties lead to the production of confabulation. They are inconsistent with the idea that memory monitoring impairment is necessarily involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…More specifically, Morais et al (2004) showed that confabulation in schizophrenia patients was higher for fables than stories, and higher for stories than word lists, but was unrelated to memory monitoring failure. Schizophrenic confabulations are also found to be associated with conceptual disorganization (Salazar-Fraile et al, 2004), and they exhibit difficulty in distinguishing plausible from implausible information in fables (Nathaniel-James et al, 1996).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…More specifically, Morais et al (2004) showed that confabulation in schizophrenia patients was higher for fables than stories, and higher for stories than word lists, but was unrelated to memory monitoring failure. Schizophrenic confabulations are also found to be associated with conceptual disorganization (Salazar-Fraile et al, 2004), and they exhibit difficulty in distinguishing plausible from implausible information in fables (Nathaniel-James et al, 1996).…”
Section: Resultsmentioning
confidence: 97%
“…This suggests the stories are represented abnormally at the encoding phase and are disorganized even before they are retrieved. This deficit is further compounded by a faulty editing process at output (see Morais et al, 2004). Schizophrenia patients’ tendency to confabulate even in the absence of a memory component further supports the role of faulty encoding processes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations